2011
DOI: 10.1007/s13233-011-1004-8
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized PLGA-based scaffolds and their osteogenic potential with bone marrow stromal cells

Abstract: A cell-derived extracellular matrix (ECM) was naturally obtained and its effect on the induction of osteogenesis of bone marrow stromal cells (BMSCs) was investigated. Once porous composite scaffolds made of poly(Llactic-co-glycolic acid) (PLGA), hydroxyapatite (HA), and β-tricalcium phosphate (β-TCP) were fabricated, these scaffolds were seeded with fibroblasts or preosteoblasts and cultured in vitro. They were then subjected to decellularization, resulting in fibroblasts-decellularized scaffolds (FDS) or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Subcutaneous implants of polyesterurethane scaffolds coated with mineralized osMSC-derived ECM induced the ingrowth of host cells and the formation of a mineralized matrix that stained positive for bone sialoprotein (BSP), whereas no mineralization or BSP was found in the uncoated polymer scaffold explants 31 . Similarly, Hong et al demonstrated enhanced osteogenic differentiation of naïve MSCs implanted on PLGA/HA/β-TCP scaffolds coated with fibroblast-CDM using a subcutaneous ectopic bone formation model 28 . Explanted matrix-coated scaffolds had greater collagen and calcium deposition and ALP expression than uncoated scaffolds 28 .…”
Section: Cell-derived Matrices In Skeletal Tissue Engineeringmentioning
confidence: 90%
See 3 more Smart Citations
“…Subcutaneous implants of polyesterurethane scaffolds coated with mineralized osMSC-derived ECM induced the ingrowth of host cells and the formation of a mineralized matrix that stained positive for bone sialoprotein (BSP), whereas no mineralization or BSP was found in the uncoated polymer scaffold explants 31 . Similarly, Hong et al demonstrated enhanced osteogenic differentiation of naïve MSCs implanted on PLGA/HA/β-TCP scaffolds coated with fibroblast-CDM using a subcutaneous ectopic bone formation model 28 . Explanted matrix-coated scaffolds had greater collagen and calcium deposition and ALP expression than uncoated scaffolds 28 .…”
Section: Cell-derived Matrices In Skeletal Tissue Engineeringmentioning
confidence: 90%
“…Similarly, Hong et al demonstrated enhanced osteogenic differentiation of naïve MSCs implanted on PLGA/HA/β-TCP scaffolds coated with fibroblast-CDM using a subcutaneous ectopic bone formation model 28 . Explanted matrix-coated scaffolds had greater collagen and calcium deposition and ALP expression than uncoated scaffolds 28 . The increased osteogenic differentiation of implanted MSCs was attributed primarily to instructive cues present in the CDM, as the MSC were not treated with soluble exogenous osteogenic factors prior to implantation.…”
Section: Cell-derived Matrices In Skeletal Tissue Engineeringmentioning
confidence: 90%
See 2 more Smart Citations
“…Decellularization involves the removal of cells, keeping intact the other ECM components in tissues or organs [15]. Decellularized ECM (dECM) produced by this technique has been used in tissue engineering applications because it mimics the natural tissue microenvironment by providing bioactive components, such as growth factors and cytokines [16][17][18][19][20]. dECM has also been used in various cancer studies as a scaffold to provide a microenvironment for the 3D culture of cancer cells.…”
Section: Introductionmentioning
confidence: 99%